The Development of FunLABS Android-Based Application Using Unity Software as Learning Media to Explore Students’ Motivation on Acid, Base, and Salt Topic - Yulianita Nursakinah; Eka Cahya Prima; Rika Rafikah Agustin (Journal of Science Learning, 2023)
The lack of digital media to support middle school chemistry learning needs further expanded. Hence, an Android application as a learning media on acid, base, and salt topics was needed. This study aims to develop FunLABS (Fun Learning Acid, Base, and Salt) android-based applications. This study used a DDD-E model of development as a research method, and it consists of deciding stage, designing stage, developing stage, and evaluating stage. The deciding stage begins with analyzing the content and the software developed. The design stage consists of drawing a flowchart and the storyboard. Then, in the developing stage, the application was developed based on the previous stage. The last is the evaluation stage, which involves three expert judges, three science teachers, and forty students chosen to review the application by convenience sampling. The results from the expert's judgment show an average score of 3.54. The results from teachers show an average score of 3.49. The results from students show an average score of 3.51. The profile of students' motivation score after operating the FunLABS Application is 77.87% which is described as good motivation. Hence, the results from the experts, science teachers, and students showed positive feedback, and the application was completely revised. The FunLABS Android application can be used in the learning activity to explore students' motivation on acid, base, and salt topics.